Positifikasi Hukum Keluarga di Dunia Muslim melalui Pembaharuan Hukum Keluarga - Moh. Nasrun; Sulthon Fathoni (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2020)
Abstract This study is about the economic potential offered by KONSAIN (Indonesian Santri Agribusiness Contact). KONSAIN was established to build funding sources for educational institutions, da'wah institutions and social institutions, for the sake of education, da'wah and social throughout Indonesia through the development of oil palm plantation started from East Kalimantan. This study will use a descriptive-analytical approach by analyzing the progress of the number of members, member types, and the origin of members. It is to see the potential for future development and the extent to which it will survive. This study also seeks to see its endurance from the legal side as an institution. From this study it can be concluded that the growth in the number of members fluctuates, not constantly rising or falling. The origin of the members also spread throughout Indonesia but the majority came from East Kalimantan and East Java. The obstacle is the number of fraudulent investments in stocks, capital, and the time of division of SHU which is considered too long. Abstrak Kajian ini adalah tentang potensi ekonomi yang ditawarkan oleh KONSAIN (Kontak Santri Agribisnis Indonesia). KONSAIN didirikan untuk membangun sumber dana bagi lembaga pendidikan, lembaga dakwah dan lembaga sosial, untuk kepentingan pendidikan, dakwah dan sosial se Indonesia melalui pembangunan kebun kelapa sawit yang dimulai dari Kalimantan Timur. Kajian ini akan menggunakan pendekatan deskriptif-analisis dengan menganalisa perkembangan jumlah anggota, jenis anggota, dan asal anggota. Hal itu untuk melihat potensi perkembangannya di masa depan dan sejauh mana akan bertahan. Kajian ini juga mencoba melihat ketahanannya dari sisi hukum sebagai sebuah institusi. Dari kajian ini bisa disimpulkan bahwa pertumbuhan jumlah anggota fluktuatif, tidak konstan naik atao turun. Asal anggota juga menyebar di seluruh Indonesia tetapi mayoritas berasal dari Kaltim dan Jatim. Hambatannya adalah banyaknya penipuan penanaman saham, modal, dan masa pembagian SHU yang dianggap lama.